PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMPENSASI, DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PADA DINAS SOSIAL PROVINSI KOTA YOGYAKARTA BIDANG OPERASONAL - Sugeng Widodo (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to describe: (1) the influence of transformational leadership on job satisfaction; (2) the effect of compensation on job satisfaction; (3) the influence of work motivation on job satisfaction; (4) the influence of transformational leadership, compensation and work motivation together on job satisfaction This research is a quantitative research. The population in this study are employees of